Analisis Perhitungan Harga Pokok Produksi Menggunakan Metode Full Costing Pada Konveksi Gapions Productions: Analysis of Production Cost Calculation Using the Full Costing Method at Gapions Productions Convection - Afghan Rabbani; Nisya Putri Fakha Sari; Nurul Izzati; Sesa Diah Islami; Tri Lestari (Jurnal Mnajemen | Ekonomi | Akuntansi, 2025)
Gapions Productions is a convection company that produces clothes. The purpose of this research is to analyze the cost of goods manufactured at Gapions Productions Convection using the full costing procedure. The variable of this research is the cost of goods at Gapions Productions Convection using the full costing procedure. The subject of the author's research is the owner of Gapions Productions Convection. The main focus of this analysis is related to the initial price of goods. Gapions Productions by using the full costing method. Data is collected through documentation and interview process. Data analysis techniques are carried out through qualitative descriptive analysis methods. By examining the results, it can be determined that the total production cost calculated using the full costing method accurately for 1,100 pieces of clothes at Gapions Productions Convection is Rp 46,200,000.00 with a cost of goods per piece of clothes of Rp 42,000/piece.